Redefining Media Relations in the Age of AI-Generated Summaries: A Conceptual Framework for Digital Media Sustainability - Harun, Rusita Nurna Aulia; Komariah, Siti; Widyawati, Selviana Natalia; Kusumaningrum, Ismi Muchlisiawati; Subrata , Pramudya Ibnu (Jurnal Genesis Indonesia, 2026)
The digital communication ecosystem is undergoing a fundamental shift from link-based search systems to generative, answer-based information synthesis, creating a “zero-click” phenomenon that threatens the economic sustainability of traditional media. This conceptual research formulates a new strategic framework termed “Symbiotic Media Relations” to mitigate systemic risks for both public relations (PR) practitioners and digital media entities. Employing an integrative review approach and conceptual mapping, this study synthesizes academic literature and industry trends from 2024 to 2026, including an analysis of Indonesia’s Presidential Regulation No. 32 of 2024. The findings indicate that traditional visibility metrics, such as page views and raw impressions, have become obsolete in an era where AI-generated summaries satisfy audience cognitive needs directly. Consequently, this research proposes a reconstruction of the value exchange between PR and media, shifting from transactional publicity to a “Symbiotic Data Supply Chain.” This model suggests that PR practitioners must act as primary information infrastructure providers, supplying high-quality, structured data to enhance media content authority within generative AI architectures. The study introduces “Brand Citation Authority” (BCA) and Generative Engine Optimization (GEO) as essential competencies for maintaining narrative integrity and brand attribution. By fostering reciprocity and data transparency, the proposed framework ensures the financial resilience of high-quality journalism while securing corporate information authority. Ultimately, this research provides a strategic roadmap for navigating the automated information landscape, emphasizing that the survival of independent journalism is an ethical responsibility and a vital interest for the public relations industry in 2026.